2021
DOI: 10.1002/bies.202100187
|View full text |Cite
|
Sign up to set email alerts
|

Keeping intracellular DNA untangled: A new role for condensin?

Abstract: The DNA‐passage activity of topoisomerase II accidentally produces DNA knots and interlinks within and between chromatin fibers. Fortunately, these unwanted DNA entanglements are actively removed by some mechanism. Here we present an outline on DNA knot formation and discuss recent studies that have investigated how intracellular DNA knots are removed. First, although topoisomerase II is able to minimize DNA entanglements in vitro to below equilibrium values, it is unclear whether such capacity performs equall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 108 publications
0
9
0
Order By: Relevance
“…However, we also considered whether the activity of Topo II is regulated during G1. Specifically, yeast minichromosome experiments have shown that condensin-mediated loop extrusion biases Topo II towards disentangling minichromosomes 84,85 . Computational modeling also suggests that a mechanism of loop extrusion, by cohesin or condensin, could bias Topo II towards untangling chromosomes 83 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we also considered whether the activity of Topo II is regulated during G1. Specifically, yeast minichromosome experiments have shown that condensin-mediated loop extrusion biases Topo II towards disentangling minichromosomes 84,85 . Computational modeling also suggests that a mechanism of loop extrusion, by cohesin or condensin, could bias Topo II towards untangling chromosomes 83 .…”
Section: Resultsmentioning
confidence: 99%
“…Recent computational studies have proposed that loop extrusion by SMC complexes may bias Topo II towards disentanglement, or decatenation 97,98 . An elegant study in budding yeast on the topological state of yeast minichromosomes has identified a role for the condensin complex in this process 84,85 . We find that in cohesin depleted G1 cells, both compartment strength and long-range intra-chromosomal entanglement increases in a Topo II dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…This question is a generalization of the problem of intrachain topological entanglement, or knotting, in space-filling curves, which has bearing in biological contexts such as DNA packaging in viral capsids (46,47) and in soft matter ones related to polymers and self-assembling meta-materials in confinement (48)(49)(50)(51)(52). Extending considerations to the interlocking of self-assembled rings offers a timely reference also for challenging biological systems, such as the linked DNA ring assemblies of kinetoplasts (53) and strand crossings in DNA bundles operated by topoisomerase enzymes (44,45,54).…”
Section: Linking Probability In Space-filling Ring Meltsmentioning
confidence: 99%
“…Cohesins cannot change any topological properties of the participating DNA domains so long as no strands are cut. But they can greatly alter their sets of accessible tertiary structures ( 121 ).…”
Section: Limitations and Opportunitiesmentioning
confidence: 99%
“…Unless prevented or resolved, they may impede essential processes such as transcription, replication and chromosome separation ( 130 , 131 ). Resolving duplex crossings that otherwise would prevent correct chromatid segregation is thought to be an important function of eukaryotic TOPO2s, perhaps aided by cohesins ( 121 ). But any action that resolves duplex crossings also would tend to untie knots and braids, and unlink catenanes.…”
Section: Topology In Biologymentioning
confidence: 99%